2022
DOI: 10.1007/s00384-022-04257-w
|View full text |Cite
|
Sign up to set email alerts
|

Stoma versus anastomosis after sphincter-sparing rectal cancer resection; the impact on health-related quality of life

Abstract: Background Surgical resection is the mainstay of curative treatment for rectal cancer. Post-operative complications, low anterior resection syndrome (LARS), and the presence of a stoma may influence the quality of life after surgery. This study aimed to gain more insights into the long-term trade-off between stoma and anastomosis. Methods All patients who underwent sphincter-sparing surgical resection for rectal cancer in the Leiden University Medical Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…However, the LARS score was not formally measured in this study [25,26]. It has been shown that quality of life in patients reporting LARS is significantly impaired [27,28]. Patients with a stoma also reported specific stoma-related challenges, such as worrying about stool leakages and uncontrollable flatulence, which is consistent with previous literature [29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the LARS score was not formally measured in this study [25,26]. It has been shown that quality of life in patients reporting LARS is significantly impaired [27,28]. Patients with a stoma also reported specific stoma-related challenges, such as worrying about stool leakages and uncontrollable flatulence, which is consistent with previous literature [29].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, as shown in this study, some patients reported that good preoperative education on the consequences of colorectal cancer treatment is important to them. Explicit patient consideration of their treatment and certain trade‐offs are shown to have a positive effect on long‐term quality of life, as it leads to increased acceptance of treatment consequences [14, 27]. As shown in this study, after colorectal cancer treatment, patients face several treatment‐related health deficits in various domains (e.g., psychological, social, physical) [22].…”
Section: Discussionmentioning
confidence: 99%
“…An important dilemma in patients undergoing sigmoid or rectal resection is whether or not to construct an anastomosis and/or (temporary) stoma. 33 An important consideration is the risk of anastomotic leakage since a (temporary) diverting stoma can reduce the rate of clinical symptomatic anastomotic leakage. 6,34 Furthermore, measuring a low muscle mass on the preoperative CE-CT could be an indication for prehabilitation programs, since low muscle mass may be reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate prediction of postoperative complications and especially anastomotic leakage could improve preoperative patient selection, treatment decision and shared‐decision making. An important dilemma in patients undergoing sigmoid or rectal resection is whether or not to construct an anastomosis and/or (temporary) stoma 33 . An important consideration is the risk of anastomotic leakage since a (temporary) diverting stoma can reduce the rate of clinical symptomatic anastomotic leakage 6,34 .…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Finally, permanent stoma might be inevitable after failure of every effort, and could improve the quality of life. 56,57 Sometimes patients who suffer from the severe symptoms of LARS strongly ask the surgeon to make the permanent stoma first. The specific care for stoma can have advantages for hygienic problems and be preferred to a devastating daily life from the frequent and urgent bowel movements or fecal incontinence with painful perianal skin irritation.…”
Section: Surgical Treatmentsmentioning
confidence: 99%